Early Life Exposure to Above Average Rainfall and Adult Mental Health - Mochamad Pasha; Marc Rockmore; Chih Ming Tan (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2018)
We study the effect of early life exposure to above average levels of rainfall on adult mental health. While we find no effect from pre-natal exposure, post-natal positive rainfall shocks decrease average Center for Epidemiological Studies Depression (CESD) mental health scores by 15 percent and increase the likelihood of depression by 5 percent, a more than 20 percent increase relative to the mean. These effects are limited to females. We rule out prenatal stress and income shocks as pathways and find evidence suggestive of increased exposure to disease.
Keywords: I15; O12; 330; Fetal origins; early life shocks; rainfall; mental health; climate change; Indonesia